Associação entre o controle glicêmico em diferentes aspectos emocionais e a adesão à contagem de carboidratos em pessoas com diabetes tipo 1 durante a pandemia por Covid-19 no Brasil - VIANA, Vandemberg Ramos (2023)
People with Type 1 Diabetes Mellitus (T1DM) are among risk groups for the development of more severe COVID-19 conditions, which may be related to the deficiency in glycemic control. Carbohydrate Counting (CC) is a strategy that aims to ensure improved quality of life for individuals with T1DM, as it allows flexibility in eating habits. If there is a low adherence to the treatment of T1DM, the complications of the disease can compromise the biopsychosocial conditions of individuals. Objective: To evaluate the association between glycemic control in different emotional aspects and adherence to CC in people with T1DM during the COVID-19 pandemic in Brazil. Methodology: This is a cross- sectional, descriptive and analytical study, carried out in July 2020. Data collection was through Google Forms®. Socioeconomic and demographic data; glycemic monitoring according to the individuals' emotions at the time of measurement (when happy, motivated or hopeful; when stressed or anxious; when sad, distressed or with depressive symptoms); information regarding adherence to CC and social distancing were collected. For data analysis, it was use independence’s Chi-Square test with adjusted residues analysis. The research was approved by the ethics and research committee (number 4.147.663). Results: 472 people were evaluated, the majority were female (n = 406; 86.02%; p <0.000). Associations were observed in all emotional aspects with presenting “normoglycemia” and performing CC (p<0.000); and “not measuring blood glucose” because it did not have the necessary supplies, it was associated with not performing CC (p<0.000). Furthermore, when the participants felt happy, motivated or hopeful, “having hyperglycemia” and “not measuring blood glucose”, they were associated with not performing CC (p <0.000). Conclusion: It is important to highlight the need to encourage adherence to CC, as a way of making the food routine more flexible, potentiating the autonomy of patients, and, in addition, the importance of multi-professional assistance regarding the mental health of these individuals.